Investigating the growth-promoting effects of entophytic fungi isolated from Camellia luteflora on tomato seedlings - Bai, Xiaojie; Yan, Pingping; Guo, Chunxia; Yi, Hang; Liu, Bangyou; Wang, Li (Frontiers in Microbiology, 2025)
Camellia luteflora, an endangered plant species native to China, faces significant conservation challenges due to its limited habitat and vulnerability to pathogens. Investigating the entophytic fungal communities within C. luteflora, particularly those that promote plant growth and stress resilience, is crucial. Through systematic evaluation, the growth-promoting ability of entophytic fungi from C. luteflora and the effects of inoculation on the growth of tomato seedlings were investigated. Among the 35 isolated entophytic fungi, 7 strains exhibited the ability to synthesize indole-3-acetic acid (IAA), 24 strains showed nitrogen-fixing abilities, 27 strains were capable of producing protease, and 15 entophytic strains had a siderophore utilization (SU) value exceeding 10.00%. Furthermore, five strains were identified as capable of potassium solubilization, and seven strains as phosphorus solubilizers. Three strains demonstrated a dual ability for phosphorus and potassium solubilization. The entophytic fungal inocula derived from entophytic fungi CG-II-1, CJ-V-1, and DJ-I-4 resulted in significant enhancement of chlorophyll content in tomato seedlings, as well as promoting root development and biomass accumulation. This study found that CJ-V-1 (Colletotrichum siamense) and CG-II-1 (Helotiales sp.) have significant potential for promoting plant growth, creating opportunities for utilizing these strains as innovative resources for entophytic fungal inocula development.